Pengaruh Cuaca Terhadap Perilaku Pengendara Sepeda Motor di Daerah Istimewa Yogyakarta - Ismaili, Abul Fida (Universitas Muhammadiyah Yogyakarta, 2017)
Indonesia as a developing country has a considerable growth in motor vehicles. Unlike other countries, the growth of motor vehicles is quite large motorcycle. In the last few years, the study of the relationship between weather and transportation is mostly done in the region or country with four seasons different in climate condition or in developed countries with good public transport conditions. It is still few to do research in developing countries, with poor public transport conditions and other problems. Yogyakarta is a city with tropical climate that it only has two types of weather conditions, namely dry and rainy seasons, which the bothÂ will affect motorcyclists in Yogyakarta becoming the majority. In this study,Â the author used a qualitative and quantitative approach to find the impact of weather changes on motorcyclists' travel behavior. From the results of the study, it was found that the number of motor users was reduced by more than 30% when the weather changed. Broadly speaking, there are three behaviors of motorcyclists when the weather changes namely, wait until the weather back to normal, cancel the trip and continue the journey however in the conditions due to some reasons.